The use of radon (Rn-222) and volatile organic compounds in monitoring soil gas to localize NAPL contamination at a gas station in Rio Claro, Sao Paulo State, Brazil - Barbosa, E. Q. [UNESP]; Galhardi, J. A. [UNESP]; Bonotto, D. M. [UNESP] (Elsevier B.V., 2014)
This study focuses on the presence of radon (Rn-222) and volatile organic compounds (VOCs) in soil gases at a gas station located in the city of Rio Claro, Sao Paulo, Brazil, where a fossil fuel leak occurred. The spatial distribution results show a correlation between Rn-222 and VOCs, consistent with the fact that radon gas has a greater chemical affinity with organic phases than with water. This finding demonstrates that the presence of a residual hydrocarbon phase in an aquifer can retain radon, leading to a reduced radon content in the soil gas. The data in this study confirm the results of previous investigations, in which the method used in this study provided a preliminary fingerprint of a contaminated area. Furthermore, the data analysis time is brief, and only simple equipment is required. (C) 2014 Published by Elsevier Ltd.
Keywords: Radon; Volatile organic compounds; Subsurface contamination; NAPL